The Effect of Oxygenation on Improving Breathing Pattern in Congestive Heart Failure Case - Naura Dian Fadila; Prasanti Adriani; Arni Nur Rahmawati (Inspirasi Foundation, 2022)
Objective: To determine the effect of oxygenation on increasing ineffective breathing patterns in congestive heart failure (CHF). Method: This case study uses a descriptive method that includes an assessment that aims to provide a detailed description of the background, nature and character of a case. This study uses three data collection techniques, namely, primary data (interviews and observations), and secondary data (documentation). Result: After giving oxygen, the results showed that there was a change in breathing pattern for the better, no shortness of breath, and a normal frequency of respiration 21 x/minute and SPO2 99%. Conclusion: It is concluded that the ineffective breathing pattern can be overcome by giving oxygenation. It can be seen from the results of the research evaluation that giving oxygen before and after can have an effect on improving breathing.